Rare encounter: Adult-onset temporal lobe schizencephaly with septo-optic dysplasia - a case report on comprehensive diagnosis and management - Sundar Suwal, MD; Shailendra Katwal, MD; Dinesh Chataut, MD; Suman Lamichhane, MD; Aayush Adhikari, MBBS; Pratik Baral, MBBS; Amrit Bhusal, MBBS (Radiology Case Reports, 2024)
This case report presents a 21-year-old male with recurrent seizures attributed to isolated temporal lobe closed-lip schizencephaly coexisting with septo-optic dysplasia. Despite adult-onset seizures, the patient lacked motor deficits, maintaining normal developmental milestones. Comprehensive diagnostic modalities, including MRI revealing temporal lobe atrophy and associated abnormalities, contributed to the unique identification of schizencephaly. The classic triad of septo-optic dysplasia further complicated the clinical spectrum. Financial limitations influenced the predominantly conservative management, highlighting healthcare challenges. This case enhances our understanding of the rare congenital disorder, emphasizing the importance of tailored diagnostics and management strategies for diverse presentations of schizencephaly, particularly in the context of associated congenital anomalies.